Recent Developments on Precise Timing with the PICOSEC Micromegas Detector. (April 2020) - Manthos, I; Bortfeldt, J; Brunbauer, F; David, C; Desforge, D; Fanourakis, G; Franchi, J; Gallinaro, M; García, F; Giomataris, I; Gustavsson, T; Guyot, C; et al.
Abstract: The PICOSEC-Micromegas detector was developed for precise timing of the arrival of charged particles with a resolution bellow 30 ps. This contribution, after a brief introduction presents results concerning the PICOSEC-Micromegas response to single photoelectrons, estimation of the photoelectron yield of various photocathode types, as well as its performance to time the arrival of test beam muons. In addition, results based on detailed simulation studies and a stochastic model developed for the understanding of the detector are presented. Finally, results of studies related to the development of large scale PICOSEC-Micromegas detector for practical applications are also presented, in particular, the timing performance of a multi-channel PICOSEC prototype.